Parkinson’s PLUS Imaging: Pictorial Review from Neuroradiology Department of RABAT - El Ouali, Ibtissam; Berrada, Kenza; El Graini, Soumya; Elkettani, Najwa Elcherif; Fikri, Meriem; Jiddane, Mohamed; Touarsa, Firdaous (British Journal of Healthcare and Medical Research, 2025)
Parkinsonian syndrome includes a group of heterogenous neurodegenerative disorders known as parkinsonian-plus syndromes. These variants present few similar characteristics with Parkinson’s disease. However, they have distinguishing clinical presentation and pathophysiology which explains the variety of imaging features that we will be reporting in details in this review to facilitate identification of certain specific patterns of each form.